Clinical Characteristics of PMS Co-Morbid with MDD and Effectiveness of SSRIs in its Treatment - Yakimova R. (Sciendo, 2020)
Background: Data on the clinical characteristics of premenstrual syndrome (PMS) with co-morbid major depressive disorder (MDD) are scarce. Although selective serotonin re-uptake inhibitors (SSRIs) are widely used to treat both PMS and MDD there is little information on their efficacy in PMS in patients with co-morbid MDD.